Advancements in Welding Technology: A Comprehensive Review of Techniques, Materials, and Applications - Rahadian N (Journal PEP Bandung, 2025)
Welding is a critical process in engineering structure fabrication, and advancements in technology have enhanced its efficiency, quality, and safety. This paper presents a comprehensive review of the latest welding techniques, materials, and applications. It covers various processes like arc welding, laser welding, friction welding, and ultrasonic welding. Materials such as metals, plastics, and composites used in welding are discussed, alongside applications in aerospace, automotive, and construction industries. The future direction of welding technology and its impact on industry and society is also explored. The review begins with an overview of the evolution of welding techniques, including traditional methods like shielded metal arc welding and gas metal arc welding, as well as advanced techniques like laser welding and friction stir welding. Each technique's advantages, limitations, and application areas are examined, highlighting their effectiveness across industries. Furthermore, the paper discusses advancements in welding materials, such as high-strength alloys, composites, and specialized coatings. Their impact on weldability, mechanical properties, and corrosion resistance is evaluated, along with their applications in specific industries. The study also investigates a wide range of welding applications in automotive manufacturing, shipbuilding, oil and gas pipelines, and aerospace engineering. Specific requirements and challenges for each application are addressed, along with commonly used welding techniques and materials. In conclusion, this comprehensive review showcases significant advancements in welding technology and their implications for various industries. It underscores the importance of staying updated with the latest techniques and materials to optimize welding processes, improve product quality, and ensure the safety and reliability of welded structures. This paper serves as a valuable resource for researchers, engineers, and industry professionals seeking to enhance their understanding of welding technology and explore its vast potential in different applications.